Impact of Alarm Frequency on Dialysis Adequacy using Online Clearance Monitor System in Haemodialysis Machine: A Cross-sectional Study - S Swadeeshwaran; P Hemanth; Aksa Shibu (Journal of Clinical and Diagnostic Research)
Introduction: Haemodialysis (HD) adequacy is critical for patient outcomes. Alarms frequently interrupt treatments, making it important to understand the relationship between alarm frequency and dialysis adequacy (Kt/V). Aim: To evaluate the impact of HD machine alarm frequency on dialysis adequacy using the Online Clearance Monitor (OCM). Materials and Methods: This cross-sectional study was conducted at the Dialysis Unit of Yenepoya Medical College Hospital, Mangaluru, Karnataka, India, from September 2023 to May 2024, involving 43 HD patients. OCM was used to determine HD adequacy. Data such as postdialysis weight, haemoglobin, Kt/V goal achievement and alarm occurrences during the four-hour session on Fresenius 4008S machines were collected. Regression analysis was employed to examine the association between adequacy and alarm frequency. Results: The study population comprised 12 females and 31 males, with a mean age of 51.44±15.822 years. The mean frequency of alarm muting was 2.02±2.858 times per treatment, with an average achieved Kt/V of 1.251±0.088. Conductivity alarms were the most frequent (mean±SD=4.55±3.83), followed by upper and lower vein alarms. Multiple linear regression analysis revealed a statistically significant positive association between alarm muting frequency and Kt/V values {β=0.010, 95% CI (0.0011, 0.0195), p-value=0.0282}. Conclusion: The study found that increased alarm muting frequency was associated with improved dialysis adequacy, as measured by Kt/V. This suggests that selective alarm muting based on clinical judgment may not negatively impact treatment effectiveness. However, further research is needed to establish optimal protocols for alarm management that balance treatment efficiency with patient safety.